Cinema in the borders of the world: economic reflections on Pathé and Gaumont film distribution in Latin America (1906-1915) - Julio Lucchesi Moraes (Cahiers des Amériques Latines)
Ever since the first theoretical reflections on Latin American Film History, a central role has been given to foreign economic agents. Curiously, very few researches advanced in the comprehension of the effective role performed by these social actors. This article wishes to understand some of the methods employed by the hegemonic film industries Pathé Frères and Société des établissements Gaumont to enter and conquer Latin American markets at the dawn of the 20th century. By analysing commercial data gathered from international archives, we intend to revisit some of the debates over the peripheral and/or dependent condition of the Latin American cultural sector.